THE RE-ORIENTALISED COSMOPOLITAN TURN IN YANGSZE CHOO’S “THE GHOST BRIDE” - DALAL, Sanghamitra; NEO, David H.J. (Studia Universitatis Babeș-Bolyai Philologia, 2022)
The Re-Orientalised Cosmopolitan Turn in Yangsze Choo’s The Ghost Bride. The magical realist bestseller The Ghost Bride (2013) by Yangsze Choo was adapted into a Netflix original series in 2020. The story revolves around the female protagonist, Pan Li Lan, whose hand has been requested to wed the late Lim Tian Ching, making it a “ghost marriage” or “spirit wedding,” and her, a ghost bride. With the financial woes that the Pan family is facing, Li Lan has to carefully consider this macabre proposal by the wealthy and prominent Lim family. In this article, the authors look at the novel and the Netflix series, The Ghost Bride and argue that it is a form of re-orientalised metropolitan cosmopolitanism, contrived for global consumption in the current global cultural marketplace. Set in 1893, in the colonial cosmopolitan port city of Malacca, the production employs the elite culture of the Peranakan Chinese and re-orientalises it. The critics will, therefore, examine the dynamics of re-orientalism and cosmopolitanism and eventually contend that the production of The Ghost Bride manifests a re-orientalised cosmopolitan turn in depicting a local culture for a global audience. Article history: Received 22 May 2022; Revised 15 August 2022; Accepted 20 August 2022; Available online 20 September 2022; Available print 30 September 2022. REZUMAT. Turnura cosmopolită re-orientalizată în The Ghost Bride de Yangsze Choo. Bestsellerul magic-realist The Ghost Bride (2013) de Yangsze Choo a fost adaptat într-un serial original difuzat de Netflix în anul 2020. Când mâna protagonistei Pan Li Lan este cerută de răposatul Lim Tian Ching, perspectiva devine aceea a unei “căsătorii fantomatice” sau a unei “nunți spiritiste,” cu ea ca mireasă fantomă. Date fiind problemele financiare cu care se confruntă familia Pan, Li Lan se vede nevoită să ia în considerare propunerea macabră a bogatei și puternicei familii Lim. Prezentul articol discută seria ecranizată de Netflix după romanul The Ghost Bride ca o formă de cosmopolitism metropolitan re-orientalizat, conceput pentru consumul global pe piața culturală globală actuală. Amplasată în Malacca, oraș-port colonial cosmopolit în anul 1893, producția exploatează cultura de elită a comunității chineze Peranakan și o re-orientalizează. Vom examina, așadar, dinamica re-orientalismului și cosmopolitismului cu intenția de a demonstra că producția The Ghost Bride marchează o turnură cosmopolită re-orientalizată în reprezentarea unei culturi locale pentru un public global. Cuvinte-cheie: re-orientalism, cosmopolitism metropolitan, realism magic, chinezi Peranakan, The Ghost Bride